Analysis of possibilities and proposals of intelligent transport system (ITS) implementation in Lithuania - Jarašūniene, Aldona (Transport, 2006)
ITS covers all modes of and considers all elements of the transportation system - the vehicle, the infrastructure, and the driver or user, interacting together dynamically. Information is at the core of ITS whether it is static or real‐time traffic data or a digital map. Many ITS tools are based on the collection, processing, integration and supply of information. Data generated by ITS may provide real‐time information about current conditions on a network, or on‐line information for journey planning, enabling highway authorities and agencies, road operators, public and commercial transport providers and individual travellers to make better informed, safer, more coordinated and more ‘intelligent’ decisions or ‘smarter’ use of networks. There are studies showing estimation of ITS implementation in foreign countries and in Lithuania, ITS vision, the conclusions of SWOT analysis, possible technical solutions of ITS deployment, ITS planning and financing and measures of ITS deployment in Lithuania.First Published Online: 27 Oct 2010